2016
DOI: 10.18632/oncotarget.14029
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase II study of salvage photodynamic therapy using talaporfin sodium (ME2906) and a diode laser (PNL6405EPG) for local failure after chemoradiotherapy or radiotherapy for esophageal cancer

Abstract: Photodynamic therapy (PDT) showed promising efficacy for local failure after chemoradiotherapy (CRT) for esophageal cancer. However, PDT required long sun shade period. This study aimed to evaluate the safety and efficacy of PDT using second generation photosensitizer, talaporfin sodium for local failure after CRT. This was the multi-institutional non-randomized phase II study. Patients with histologically proven local failure limited within the muscularis propria after 50Gy or more radiotherapy (RT) for esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 28 publications
3
114
0
1
Order By: Relevance
“…Progression‐free survival and overall survival for 113 patients treated with salvage PDT were 22.1 and 35.9%, respectively, for a mean follow‐up period of 5 years, with low phototoxicity rates . A recent study showed 88.5% (95% CI 69.8%‐97.6%) of 23 patients achieving local complete response after salvage PDT with talaporfin sodium and a diode laser, with no skin phototoxicity observed . These studies demonstrate increasing promise of talaporfin sodium PDT as a potential curative salvage treatment for patients failing CRT.…”
Section: Efficacy For Solid Tumorsmentioning
confidence: 78%
“…Progression‐free survival and overall survival for 113 patients treated with salvage PDT were 22.1 and 35.9%, respectively, for a mean follow‐up period of 5 years, with low phototoxicity rates . A recent study showed 88.5% (95% CI 69.8%‐97.6%) of 23 patients achieving local complete response after salvage PDT with talaporfin sodium and a diode laser, with no skin phototoxicity observed . These studies demonstrate increasing promise of talaporfin sodium PDT as a potential curative salvage treatment for patients failing CRT.…”
Section: Efficacy For Solid Tumorsmentioning
confidence: 78%
“…After that, a phase I study of talaporfin PDT to find the adequate laser dose for esophageal cancer was conducted, and no patient experienced severe adverse events or phototoxicity, supporting the establishment of 100 J/cm 2 as the recommended dose for treating local failure after CRT . Subsequently, a multi‐institutional phase II study to acquire regulatory approval was conducted in Japan . The PDT procedure commenced with i.v.…”
Section: Talaporfin Pdt For Local Failure After Crtmentioning
confidence: 96%
“…Therefore, in the trial of PDT using talaporfin sodium patients with baseline T4 aorta invasion before radiotherapy or lesions larger than 3 cm or half circumference of lumen were excluded. According to the revised criteria, no cases of esophageal perforation or stricture were reported in the trial of PDT with talaporfin sodium …”
Section: Major Complication and Side‐effects Due To Pdt For Esophageamentioning
confidence: 99%
See 2 more Smart Citations